Metastatic Merkel cell Carcinoma: Case Report: Carcinoma de Merkel - Schoeler, Nathielen Caroline (2021)
Introduction: The Merkel cell carcinoma is a rare cutaneous neuroendocrine tumor that originates from cells responsible for tactile sensitivity, it has an aggressive character, fast evolution and difficult treatment. Case report: 49 years Caucasian male patient, with a painless nodule, infiltrating deep tissue, not ulcerated and located in left arm identified during the dermatological consultation. The result of the incisional biopsy was positive for Merkel cell carcinoma. After resection of the lesion, complementary exams revealed metastatic disease in the axilla and chest wall. The chemotherapy treatment brought an initial improvement with tumor reduction, however, it was not durable, because new areas with tumor metastases in upper regions of the body were revealed, the patient was submitted to an another surgical procedure, after which a new chemotherapy regimen failed. Conclusion: At the time of the treatment of this patient, monoclonal antibodies, such as avelumab, were not available. Early diagnosis with immediate lesion excision surgery, before the involvement of other regions, remains the best option for a better prognosis. However, regardless of this, because of the limitations at the time of the treatment, the patient died.